Early pregnancy exposure to beta-cypermethrin compromises endometrial decidualisation in mice via downregulation of cyclin D3, CDK4/6, and p21. (November 2022) - Zhou, Yong-Jiang; Geng, Yan-Qing; Gao, Ru-Fei; Liu, Xue-Qing; Chen, Xue-Mei; He, Jun-Lin
Abstract: Beta-cypermethrin (β-CYP) is a highly effective broad-spectrum insecticide that can potentially affect female reproduction. However, little is known about the effect of β-CYP on uterine decidualisation, which is a vital process by which the uterus provides a suitable microenvironment for pregnancy maintenance. Therefore, we focused on the effect and mechanism of β-CYP on endometrial decidualisation during early pregnancy in mice. The results indicated that the expression levels of HOXA10, BMP2, and IGFBP1 was significantly downregulated in the decidual tissue and primary endometrial stromal cells of pregnant and pseudopregnant mice following β-CYP treatment. Serum E2 concentration was significantly increased, whereas P4 concentration and oestrogen receptor (ERα) and progesterone receptor (PRA) expression were significantly downregulated following β-CYP exposure. The number of polyploid decidual cells was lower in the β-CYP-treated group. Furthermore, β-CYP significantly downregulated the protein expression levels of CDK4 and CDK6, and the mRNA expression levels of cyclin D3 and p21. The number of foetuses per female in the first litter was markedly reduced following exposure to β-CYP. In summary, early pregnancy exposure to β-CYP may result in defective endometrial decidualisation via compromised proliferation of uterine stromal cells and reduced expressions of cyclin D3, CDK4/6, and p21 in mice. Graphical abstract: Image 1 Highlights: β-CYP administration inhibited the proliferation of uterine stromal cells in mice. β-CYP administration lowered the number of polyploid decidual cells. β-CYP administration downregulated the expressions of cyclin D3, CDK4/6, and p21. β-CYP administration resulted in defective endometrial decidualisation. β-CYP administration resulted in abnormal fertility in pregnant mice.